A neurophenomenological theory of the three worlds. (October 2022) - Facco, Enrico
The Theory of the Three Worlds (TTW) was introduced by Popper and Eccles in 1977 in the attempt to overcome the narrow limits of materialism and determinism in the comprehension of mind–brain and inner–outer world relationships. TTW involved huge epistemological implications and raised strong criticism. Here, a new neurophenomenological version of the TTW is introduced, meeting previous criticism to the TTW. Hopefully, it may be a step toward comprehension of the mind–brain–world relationship.